The Rule of Law as a Defense Against the Threat to the Balinese Language and Script’s Extinction - I Wayan Pastika; I Gusti Ayu Agung Mas Triadnyani; I Made Suta Paramarta (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
Balinese is one of 718 local languages in Indonesia facing degradation since national and international language influences are getting stronger in the country. Bali is relatively in a better position than the others because it is supported by its speakers, the governmental laws and costumery laws, and by its own script. This article examines the form of local laws on Balinese language and its script, the implementation of the local laws on Balinese language and its script usage, and factors that determine unparallel law of language between the Balinese Provincial Government and the national government. Observation and questionnaires were applied in the data collection method, while descriptive-qualitative technique was used for the analysis. Both were guided by Language Engineering and Forensic Linguistics approaches. The article concludes that Balinese speakers and the Provincial Government work hand in hand to develop the language and its scripts